The binding of RecA protein to duplex DNA molecules is directional and is promoted by a single stranded region. - Cassuto, E (1986)
RecA protein from E. coli binds more strongly to single stranded DNA than to duplex molecules. Using duplex DNA that contains single stranded gaps, we have studied the protection by RecA protein at various concentrations, of restriction sites as a function of their distance from the single stranded region. We show that the binding of RecA protein, initiated in the single stranded region, extends progressively along the adjoining duplex in the 5' to 3' direction with respect to the single stranded region. The strand exchange reaction is known to proceed in the same direction.